基于GC-IMS分析不同提取方法对藏羊油风味的影响Influence of different extraction methods on the flavor of Tibetan sheep oil based on GC-IMS - 赵玉欣，韩丽娟，葛世鹏，孙胜男，桂林生，侯生珍，王志有，杨葆春 ZHAO Yuxin, HAN Lijuan, GE Shipeng, SUN Shengnan, GUI Linsheng, HOU Shengzhen, WANG Zhiyou, YANG Baochun (Zhongguo youzhi)
为研究不同提取方法所得藏羊油风味的差异，采用感官评价及气相色谱-离子迁移谱（GC-IMS）技术结合主成分分析（PCA）和正交偏最小二乘判别分析(OPLS-DA)对不同提取方法(湿法熬制、干法熬制、微波加热法、索氏抽提法和超声辅助酶解法)所得藏羊油挥发性化合物的差异进行分析。结果表明；湿法熬制所得藏羊油其色泽、味道和气味强度感官评价得分均较高，感官品质最好；5种藏羊油中共鉴定出42种挥发性成分，其中醛类20种(13.68%~56.56%)、醇类10种(23.62%~42.11%)、酮类5种(3.01%~34.06%)、酯类5种(1.68%~12.95%)、酸类2种(11.40%~22.13%)。PCA结果表明，索氏抽提组藏羊油的挥发性物质与其他4组藏羊油的差异较大；OPLS-DA建立的模型能够有效区分不同提取方法所得藏羊油，根据变量投影重要性(VIP)值大于1筛选出16种特征挥发性成分，分别为丙酮、乙醇、乙酸乙酯、1-己醛D、丙醛、丁醇M、1-己醛M、2-甲基丁醛、3-甲基-1-丁醇M、3-甲基丁醛、1-戊醇、丁醇D、丁醛M、乙酸M、正戊醛M和丁醛D。综上，不同提取方法所得藏羊油的风味具有差异。In order to study the differences in flavor of Tibetan sheep oil obtained by different extraction methods, the differences in volatile compounds of Tibetan sheep oil obtained by different extraction methods (wet boiling, dry boiling, microwave heating, Soxhlet extraction and ultrasound-assisted enzymatic hydrolysis) were analyzed using sensory evaluation and gas chromatography-ion mobility spectrometry (GC-IMS) technology combined with principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA). The results showed that the score of color, taste and odor intensity of Tibetan sheep oil obtained by wet boiling were higher, and the sensory quality was the best. A total of 42 volatile components were identified in the five Tibetan sheep oils, including 20 aldehydes (13.68%-56.56%), 10 alcohols (23.62%-42.11%), 5 ketones (3.01%-34.06%), 5 esters (1.68%-12.95％), and 2 acids (11.40%-22.13%). The results of PCA showed that the volatile compounds of Tibetan sheep oil in the Soxhlet extraction group were significantly different from those in other 4 groups. The model established by OPLS-DA was able to effectively differentiate between different extraction methods of Tibetan sheep oil, and 16 characteristic volatile components were screened based on the variable importance in projection (VIP) values greater than 1, which were acetone, ethanol, ethyl acetate, 1-hexanal D, propionaldehyde, butanol M, 1-hexanal M, 2-methylbutanal, 3-methyl-1-butanol M, 3-methylbutanal, 1-pentanol, butanol D, butyraldehyde M, acetic acid M, valeraldehyde M, and butyraldehyde D. In conclusion, the flavor of Tibetan sheep oil obtained from different extraction methods has differences.